"Race," rights and the law in the Supreme Court of Canada : historical case studies - Walker, James W. St. G., 1940- (Osgoode Society for Canadian Legal History : Wilfrid Laurier University Press, 1997)
Racial tolerance and a dedication to principles of justice have become part of the Canadian identity, and are often used to distinguish our historical character from that of other countries. "Race," Rights and the Law in the Supreme Court of Canada challenges this image. Four cases in which the legal issue was "race," drawn from the period between 1914 and 1955, are intimately examined to explore the role of the Supreme Court of Canada and the law in the racialization of Canadian society. Walker demonstrates that Supreme Court Justices were expressing the prevailing "common sense" about "race" in their legal decisions. He shows that injustice on the grounds of "race" has been chronic in Canadian history, and that the law itself was once instrumental in creating these circumstances. The book concludes with a controversial discussion of current directions in Canadian law and their potential impact on Canada's future as a multicultural society.
Keywords: Canada. -- Supreme Court.; Canada. -- Cour suprême.; Canada. -- Supreme Court; Kanada -- Supreme Court; Kanada / Supreme Court.; Race discrimination -- Law and legislation -- Canada -- Cases.; Race discrimination -- Law and legislation -- Canada -- History -- 20th century.; Discrimination raciale -- Droit -- Canada -- Cas, Études de.; Discrimination raciale -- Droit -- Canada -- Histoire -- 20e siècle.; LAW -- Constitutional.; LAW -- Public.; Race discrimination -- Law and legislation; Canada; Rechtsprechung; Rassendiskriminierung; Rassendiscriminatie.; Processen (rechtspraak); Discrimination raciale -- Droit -- Canada.; Canada -- Relations interethniques.; Canada. Supreme Court.; 1900-1999; Canada -- Supreme Court; Race discrimination -- Law and legislation -- Canada -- Cases; Race discrimination -- Law and legislation -- Canada -- History -- 20th century; Electronic books.; History; Trials, litigation, etc.